ANTIMICROBIAL ACTIVITY OF LEAF EXTRACT OF TWO MEDICINAL PLANTS OF BOGHORA HILL (MORIGAON) ASSAM AGAINST HUMAN PATHOGENS - DEBAJIT KALITA,; JAGAT CH. SAIKIA,; AMBARISH S. SINDAGI,; G. K. ANMOL, (The Bioscan, 2012)
The present study deals with the antibacterial activity of leaf extracts of the some medicinal plants against human pathogens. The leaf extracts of Paederia foetida and Hibiscus esculentus showed high antibacterial activity against E. coli and Staphylococcus aureus which are usually considered as facultative human pathogens. The P. foetida leaf extract showed very effective degree of Zone of Inhibition (ZOI) against growth of E. coli. Likewise H. esculentus was found fruitful against the S. aureus. Both plant leaf extracts showed very effective degree of Zone of Inhibition (ZOI) against E. coli and S. aureus.